Biochemical and Pharmacological Characterization of a Mice Model of Complex Regional Pain Syndrome. Issue 4 (July 2017) - Das, Vaskar; Kroin, Jeffrey S.; Moric, Mario; Buvanendran, Asokumar
Abstract : Background and Objectives: Complex regional pain syndrome is a challenging disease to treat. Recently, a mouse fracture model of complex regional pain syndrome has been developed that has many signs of the clinical syndrome. However, many aspects of the sensory neuron biochemistry and behavioral and pharmacological characterization of this model remain to be clarified. Methods: Mice were randomly assigned to fracture/cast or control (naive) groups. Fracture/cast mice underwent a closed distal tibia facture, with hindlimb wrapped in casting tape for 3 weeks. After cast removal, mice were tested for mechanical allodynia, burrowing behavior, and motor ability over a 12-week period. Protein immunohistochemistry was performed for substance P, calcitonin gene-related peptide, tropomyosin receptor kinase A, nerve growth factor, Nav1.7, and transient receptor potential cation-channel V1, colocalized in neurons, in the ipsilateral lumbar dorsal root ganglia (DRGs). Analgesic drugs were tested for pain-relieving efficacy. Results: Mechanical allodynia was greater in the ipsilateral hindpaw ( P = 0.0002) in the fracture/cast group versus the control group, over the 3- to 12-week period. The amount of burrowing material removed was decreased ( P = 0.0026), and there were deficits in spontaneous motor-rearing behavior ( P = 0.018). Immunostaining of substance P, calcitonin gene-related peptide, Trk A receptor, nerve growth factor, Nav1.7, and transient receptor potential cation-channel V1 all demonstrated up-regulation in the DRGs of fracture mice versus controls (all P < 0.05). Morphine, pregabalin, ketamine, acetaminophen, and dexamethasone transiently increased force withdrawal thresholds on the ipsilateral (fracture) side and improved burrowing activity after injection (all P < 0.05). Ketorolac improved only burrowing. Conclusions: Persistent pain-related behavior was demonstrated in this mouse fracture/cast model with wide-scale DRG up-regulation of pain mediators. Antihyperalgesic drugs reduced mechanical allodynia and improved burrowing.